Representações da velhice no site Maisde50 - Oliveira, Maria Lúcia Frutuoso de (2010)
It is common to relate the use of new Technologies, specially the web, to young people, executives or researchers connected to the virtual world. However, the number of people over 50 years old that use the internet has grown on the cyberspace and is becoming more common each day to find specifics sites for mature people. In this light, the aim of this dissertation is to analyze the representation constructed on the discourse about the old age on the site “Mais de 50” – http://www.maisde50.com.br/ - intending to understand more widely which images are made of aging individuals on the contemporary society. It started from the assumption that the subject emerges in/from the discourse. The discourse is of symbolic order, an effect of meaning between interlocutors, in which the representations, values and social, discursive and virtual practices circulating on the internet about aging build the identity models for those who are aging in virtual times. A transdisciplinary approach in the light of theoretical discourse analysis and poststructuralist cultural studies was adopted. The reflections are guided by authors such as Pêcheux (1997) about the imaginary formation and conditions of possibility of discursive production and reception, Foucault (1992, 1998, 2000, 2004) to issues of discursive practices and subjectivity, Hall (2002) for the identity reflection and Bauman (2007, 2005, 2003, 2001) to discuss contemporaneity, identity and new technologies, Birman (1995), Bosi (1994), Santos (2008), Peixoto and Clavairolle (2005) in relation to aging. The results show discursive practices intended to build, for an over 50 individual, a positive representation - the aging as a synonym of the best time of life. The discourses seem to erase the problems and limitations that are characteristics of aging. The internet seems to offer in this virtual space a simulacrum of a happy, health and full life, in which the “post-50” generation experiences the full realization of itself.